Amygdala, Medial Prefrontal Cortex and Glucocorticoid Interactions Produce Stress-Like Effects on Memory - Kim, Eun Joo; Kim, Jeansok J. (Frontiers in Behavioral Neuroscience, 2019)
Adverse stress effects on the hippocampal memory system are generally thought to be due to the high level of circulating glucocorticoids directly modifying the properties of hippocampal neurons and accordingly the results should be reproducible with exogenous administration of cortisol in humans and corticosterone in rodents. However, glucocorticoid levels increased to other events, such as exercise and environment enrichment, do not impair but rather enhance hippocampal memory, indicating that cortisol and corticosterone are invariant causal factors of stress. To better model the complex psychophysiological attributes of stress (i.e., aversiveness, lack of controllability, and glucose metabolism), we examined the functions of the amygdala, medial prefrontal cortex (mPFC), and corticosterone on a hippocampal-based one-trial novel object recognition (OR) memory task in rats. Specifically, animals were subjected to amygdala stimulation, mPFC inactivation, and corticosterone treatments separately or in combination during behavioral testing. Simultaneous amygdala, mPFC, and corticosterone manipulations significantly impaired OR memory comparable to behavioral stress. By contrast, individual treatments failed to reliably decrease memory functioning. These results suggest that negative mnemonic impacts of uncontrollable stress involve the amalgamation of heightened amygdala and diminished mPFC activities, and elevated circulating corticosterone level.